BANTUAN LANGSUNG TUNAI MENGATASI MASALAH DENGAN MASALAH - Umi Listyaningsih; Eddy Kiswanto (Populasi, 2009)
The government has been conducting the effort to eliminate poverty by performing several programs. One of them is Program Kompensasi Pengurangan Subsidi BBM (PKPS-BBM/Oil Subsidy Compensation Program) by giving direct cash transfer (Bantuan Langsung Tunai/BLT). BLTaims at reducing the proportion of poor people significantly. During the implementation, many problems accrured. The obstructed of information to the people during the implementation of BLT has caused the misunderstanding among the people. This eventually caused protests. The data of poor people did not reflect the real condition in the field since the limitation of village elites during the process of data collecting. The indicators to decide which people are poor were also not reflected the real condition which procured conflicts. Another impact from this miscollecting of data was that inaccuracy of target group who supposed to received BLT.